The Origin of Transylvanian Romanians in Saxon Historiography (1848-1938) - MOGA, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2025)
The paper aims to explore how the medieval history of Romanians in Transylvania is reflected in the Saxon historiography of the second half of the nineteenth century and the first four decades of the twentieth century. In order to understand the motivations behind the different historiographical perspectives and aspects related to the political and social context of Transylvania, the text contains brief references to a number of works written in different historical and social contexts, with very different authors, methodologies, presuppositions and results. Without claiming to provide an exhaustive description of the reception of this theme in Saxon historiography, the article highlights various aspects of the way in which the theme of the origins of the Transylvanian Romanians has been treated by Saxon historians, drawing attention to the heterogeneous nature of the literature devoted to this theme in the Saxon area. Finally, my research aims at answering the question of the existence of a unitary (or at least dominant) perspective in Saxon historiography on the history of the Transylvanian Romanians in the Middle Ages, interrogating the particularities of such an approach and trying to identify its position within the inter-ethnic historiographical debate on the origin of the Transylvanian Romanians. Rezumat: Lucrarea își propune să exploreze modul în care istoria medievală a românilor din Transilvania se reflectă în istoriografia saxonă din a doua jumătate a secolului al XIX-lea și din primele patru decenii ale secolului al XX-lea. Pentru a înțelege motivațiile din spatele diferitelor perspective istoriografice și aspectele legate de contextul politic și social al Transilvaniei, textul conține scurte referiri la o serie de lucrări scrise în contexte istorice și sociale diferite, cu autori, metodologii, presupuneri și rezultate foarte diferite. Fără a pretinde că oferă o descriere exhaustivă a receptării acestei teme în istoriografia săsească, articolul evidențiază diverse aspecte ale modului în care tema originilor românilor din Transilvania a fost tratată de istoricii sași, atrăgând atenția asupra naturii eterogene a literaturii dedicate acestei teme în zona germană. În final, cercetarea își propune să răspundă la întrebarea privind existența unei perspective unitare (sau cel puțin dominante) în istoriografia săsească asupra istoriei românilor din Transilvania în Evul Mediu, interogând particularitățile unei astfel de abordări și încercând să identifice poziția acesteia în cadrul dezbaterii istoriografice interetnice privind originea românilor din Transilvania. Cuvinte cheie: istorie etnică; istoriografie; studii medievale; teoria imigraționistă.